2012
DOI: 10.3371/csrp.6.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition and Visual Perception in Schizophrenia Inpatients Treated with First-and Second-Generation Antipsychotic Drugs

Abstract: We cannot conclude that SGAs were associated with better social cognition than FGAs. However, there were small but significant advantages for SGAs in non-social visual processing function, as evaluated with the VOSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Finally, Kucharska-Pietura et al [35] assessed deficits in social cognitive functioning in a naturalistic pragmatic sample of partially remitted stable schizophrenia inpatients, 28 being treated with a FGA (perphenazine or haloperidol), 56 being treated with a SGA (olanzapine or clozapine), and 50 healthy controls. In line with previous findings, there were no differences between the patient groups in emotional perception and ToM/empathy.…”
Section: Does Antipsychotic Treatment Improve Social Cognition?mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Kucharska-Pietura et al [35] assessed deficits in social cognitive functioning in a naturalistic pragmatic sample of partially remitted stable schizophrenia inpatients, 28 being treated with a FGA (perphenazine or haloperidol), 56 being treated with a SGA (olanzapine or clozapine), and 50 healthy controls. In line with previous findings, there were no differences between the patient groups in emotional perception and ToM/empathy.…”
Section: Does Antipsychotic Treatment Improve Social Cognition?mentioning
confidence: 99%
“…This is particularly striking given the supposedly superior effects of clozapine previously reported. There were small but significant advantages for SGAs in non-social low-level visual processing: this was thought to result from SGAs’ weaker antagonism of dopamine receptors in the retina [35]. …”
Section: Does Antipsychotic Treatment Improve Social Cognition?mentioning
confidence: 99%
“…Social cognition has been defined as the mental operations underlying social interactions, and is thought to represent a specialised domain of cognition, which captures affect perception, social cue perception, “theory of mind”, empathy, and attribution style [18]. As far as facial affect recognition is concerned, robust research data seemed to report less accuracy of AN patients at recognising basic facial emotions [7, 16, 21, 33].…”
Section: Introductionmentioning
confidence: 99%
“…From our PubMed search of more recent studies not included in the meta-analyses, a total of 16 of the 20 studies that examined adults with chronic schizophrenia either did not report on sex differences or controlled for sex in their FEP analyses [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] , with one study including an all-male sample [68] . Of the remaining four studies, three studies did not find sex differences on an FEP identification task [69][70][71] . By contrast, Erol et al [72] found sex differences in FEP: Chronically ill women with schizophrenia performed equivalently to men and women without schizophrenia on both identification and discrimination FEP tasks, while men with schizophrenia performed worse on both tasks.…”
Section: Adults With Chronic Schizophreniamentioning
confidence: 99%